2019
DOI: 10.1007/s00213-018-5161-8
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome and brain functional connectivity in infants-a preliminary study focusing on the amygdala

Abstract: Recently, there has been a surge of interest in the possibility that microbial communities inhabiting the human gut could affect cognitive development and increase risk for mental illness via the "microbiome-gut-brain axis". Infancy likely represents a critical period for the establishment of these relationships, as it is the most dynamic stage of postnatal brain development and a key

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 55 publications
4
95
0
Order By: Relevance
“…Some studies have attempted to assess the relationships between brain functional connectivity and gut microbiota. For example, Gao et al reported that gut alpha diversity was associated with functional connectivity between the amygdala and thalamus, between the anterior cingulate cortex and anterior insula, and between the supplementary motor area and inferior parietal lobule in infants [48]. Curtis et al showed that insular resting-state functional connectivity was related to gut microbiota diversity [33].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have attempted to assess the relationships between brain functional connectivity and gut microbiota. For example, Gao et al reported that gut alpha diversity was associated with functional connectivity between the amygdala and thalamus, between the anterior cingulate cortex and anterior insula, and between the supplementary motor area and inferior parietal lobule in infants [48]. Curtis et al showed that insular resting-state functional connectivity was related to gut microbiota diversity [33].…”
Section: Discussionmentioning
confidence: 99%
“…Of specific relevance to ecological discussions, included in DOHaD findings, is intriguing research that suggests that non-pathogenic microbes (and other aspects of biodiversity) in early life have multisystem consequences through effects on immune development [148]. One of the more fascinating dimensions of this has been revelations that this might even influence subsequent brain development and mental health [149][150][151][152]. When paired with separate research on access/residential proximity to natural environments and healthy birth outcomes (again, setting life-course health) [153,154], the psychobiological implications of rewilding loom large.…”
Section: De-extinction Of Experience Psychobiological Restoration: Mmentioning
confidence: 99%
“…Gut colonization begins at birth and the infant microbiota undergoes significant changes during the first 2‐3 years of life, before reaching a more stable condition resembling the composition of adult intestinal microbiota . During that same period, brain networks rapidly evolve, including neural circuits involved in social and emotional processing . Neonates are born equipped with reflective responses to environmental stimuli, and by the age of 3, young children will have acquired language, communicative speech, and imaginative play and will have set the foundations for the development of empathy and emotional self‐regulation …”
Section: Gut Colonization and Early Social Developmentmentioning
confidence: 99%
“…Gut microorganisms seem to communicate with the brain through multiple pathways including direct vagal stimulation, production of neuropeptides and neurotransmitters, stimulation of the HPA axis, and regulation of cytokine production . The absence of microbiota in animal models has been linked to differential gene expression and functional connectivity in brain regions implicated in social behavior such as the amygdala . Likewise, Desbonett et al showed that germ‐free mice display deficits in social motivation and social interaction, reduced preference to novel social stimuli and more repetitive behaviors.…”
Section: The Role Of Gut Microbiota In Social Behaviors: Data From Anmentioning
confidence: 99%